Heart rate and heart rate variability responses to Tai Chi and jogging in Beijing and Graz - Litscher, Gerhard (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND: Tai Chi is a famous training method in China, and jogging is a popular kind of exercise both in Austria and China. Nevertheless, there is little information concerning online monitoring of biosignals during both training activities in parallel. Within the last years innovative scientific monitoring tools for evaluating features of neurocardial fitness have been developed. AIMS: The goal of this study was to demonstrate heart rate and heart rate variability analysis for the first time during Tai Chi and jogging. VOLUNTEERS AND METHODS: Continuous electrocardiographic monitoring over a period of 75 minutes was performed simultaneously in two healthy volunteers using the same type of equipment (medilog AR12 systems). Two healthy persons (both male, 49 years and 52 years, respectively), both hobby sportsmen, were monitored continuously during two resting periods before and after active sport and also during Tai Chi and jogging, respectively. RESULTS: Data acquisition was performed without any technical problems in both subjects. Poincaré plots of sequential R-R intervals (beat to beat variability) show two ellipses of different shape and magnitude. During resting periods blood pressure effects can be clearly seen in one subject (jogging). The same effects, however reduced, are obvious in the other volunteer during Tai Chi. CONCLUSIONS: The present investigations during Tai Chi and jogging highlight the potential value of heart rate and heart rate variability monitoring even under difficult conditions. The innovative kind of analysis helps to show how well the human body reacts to sport, stress and recovery.